Body weight-length relationships in giant otters (Pteronura brasiliensis) (Carnivora, Mustelidae) - Weber Rosas, Fernando Cesar (2009)
Few giant otters (Pteronura brasiliensis) have been measured and weighed and its actual size is controversial in the literature. This study presents the weight-length relationship of Amazonian giant otters using 15 captive individuals. The maximum length and weight were 163cm and 22.5kg, and 162cm and 28.8kg, for the males and females, respectively. The weight-length relationships were not significantly different between the sexes (t = 0.658, d.f.=11, P>0.05) and can be expressed by the equation: W=1.48×10-5 L2.81. Considering that some of the giant otters used in this study were old individuals (more than 10 years old), and that all the animals analyzed were healthy, it is possible to assume that the weight-length relationships obtained are probably a close approximation of the relationship of giant otters of the Amazon region and can be used by institutions that keep this species in captivity as a base to quickly assess the animal's nutritive status. © 2009 Tecpar.